A Rare Case of Hermansky-Pudlak Syndrome Involving Bilateral Lung: Histopathologic and Electron Microscopic Findings. (11th September 2019) - Basu, Atreyee; Seshan, Surya; Angel, Luis; Moreira, Andre; Zhou, Fang
Abstract: Introduction: Hermansky-Pudlak syndrome (HPS) is a rare autosomal recessive hereditary disorder characterized by oculocutaneous albinism and bleeding diathesis. Transplantation is often conducted to treat lung fibrosis, which is the most fatal complication of this disease. While the literature discusses the diagnosis of HPS based on genetic testing, radiology, and electron microscopic (EM) findings of platelet granules, there is a paucity of images in the literature illustrating the pulmonary histopathologic and EM features of HPS. Case Report: Here we present striking histopathologic and EM images from a case of pulmonary fibrosis due to HPS in a 48-year-old female. The patient presented with restrictive lung disease and bilateral decreased breath sounds with diffuse crackles. She was clinically diagnosed with HPS and underwent bilateral lung transplant. On histopathology, both pneumonectomy specimens showed diffuse interstitial fibrosing and cellular pneumonitis with end-stage remodeling and type II pneumocyte (PC-II) hyperplasia. The PC-IIs had abundant foamy cytoplasm and compressed scalloped nuclei. Alveolar macrophages contained fine brown granules positive for PAS-D stain. EM analysis revealed that the PC-IIs contained numerous lamellated myelin bodies (so-called giant lamellar body degeneration) suggestive of surfactant admixed with lipid and luminal microvilli. The pigmented alveolar macrophages also contained lamellated myelin bodies, as well as clusters of single membrane-bound structures with varying size and electron density admixed with vacuolar and granular debris suggestive of ceroid deposits. Conclusion: Based on light microscopy, histochemical analysis, EM, and clinical presentation, it was concluded that our findings were consistent with pulmonary changes as seen in HPS.